1999
DOI: 10.1172/jci7013
|View full text |Cite
|
Sign up to set email alerts
|

The kidney cytochrome P-450 2C23 arachidonic acid epoxygenase is upregulated during dietary salt loading

Abstract: Excess dietary salt intake induces the activity of the kidney arachidonate epoxygenase and markedly increases the urinary excretion of its metabolites. The epoxyeicosatrienoic acids, products of the kidney P-450 arachidonate epoxygenase, inhibit distal nephron Na + reabsorption. Nucleic acid hybridization studies demonstrated the expression of P-450s 2C23, 2C24, and 2C11 as the predominant kidney 2C isoforms and the lack of significant dietary salt-dependent transcriptional regulation of these proteins. Recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
147
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(156 citation statements)
references
References 42 publications
7
147
2
Order By: Relevance
“…11,15 CYP2C isoforms are considered the major renal arachidonic acid epoxygenases in the kidney. In particular, CYP2C23 is highly expressed in rat kidney, where it exerts an important role in regulating EET formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,15 CYP2C isoforms are considered the major renal arachidonic acid epoxygenases in the kidney. In particular, CYP2C23 is highly expressed in rat kidney, where it exerts an important role in regulating EET formation.…”
Section: Discussionmentioning
confidence: 99%
“…Three CYP2C subfamily isoforms (CYP2C23, CYP2C24, and CYP2C11) are expressed in the rat kidney, with CYP2C23 being the predominate. 11 Recent studies showed that CYP2J protein is expressed in rat kidney, and CYP2J protein expression is increased in spontaneously hypertensive rats. 12,13 The main product of CYP2C23 isoform is 11,12-EET (57% of the products), although CYP2C11 epoxidizes the 11,12-olefins and 14,15-olefins with nearly equal efficiency.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The P450 arachidonic acid epoxygenases catalyze the metabolism of endogenous pools of arachidonic acid to 5,6-, 8,9-, 11,12-, and 14,15-EET (12)(13)(14)(15)(16)(17), a reaction catalyzed predominantly by members of the P450 CYP2C gene subfamily (12). Furthermore, CYP2C8, CYP2C23, and Cyp2c44 have been identified as predominant stereoselective epoxygenases in several human, rat, and mouse organ tissues (12,13,17,18).…”
mentioning
confidence: 99%